Empowerment of PKK Women in Tebing Tinggi Urban Village Through Counseling and Assistance in Aromatherapy Medicated Oil Production - Candra, Andy; Irfani Fitri, Fasihah; Nazriani, Dina; Veronica, Afryna (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The utilization of aromatherapy is well known by the public. The fastest-selling and accepted product is aromatherapy medicated oil. Aromatherapy products are beneficial for health to relax the body, refresh the mind, to improve mood, and as a placebo in healing diseases that have physiological effects. Aromatherapy is applied to the skin, causing essential oils to penetrate into the body's system, and then helps reduce diseases, such as depression, headaches, insomnia, muscle aches, respiratory disorders, joint disorders. By empowering the manufacture of aromatherapy medicated oil for PKK women in Tebing Tinggi Urban Village, they will be able to increase productivity in terms of economy and health. Hypothesis testing, using the Wilcoxon Difference Test with the JASP application stated that there was an increase in the knowledge of the participants of community service activities after participating it. Based on effect size, it can be concluded that service activities have a strong role in increasing participants' knowledge about aromatherapy medicated oil.